(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To synthesize high‑quality evidence on the effectiveness and indications of non‑surgical pharmacologic treatments and intra‑articular injections for hip osteoarthritis, and to propose a pragmatic, guideline‑aligned algorithm for routine care. Methods: We narratively reviewed international guidelines (OARSI 2019, ACR/AF 2019, AAOS 2023) and key evidence on intra‑articular Corticosteroids, hyaluronic acid and platelet‑rich plasma, prioritizing randomized trials and systematic reviews relevant to hip osteoarthritis. Results: Core management centers on education, weight management, and exercise; topical/oral NSAIDs and duloxetine are conditionally recommended in appropriate patients. For intra‑articular therapy, Corticosteroids provide short‑term (maximum of approximately 12 weeks) pain relief in hip osteoarthritis when accurately delivered under imaging guidance; repeated injections should be spaced and limited because of potential structural risks. Evidence for intra‑articular hyaluronic acid in hip osteoarthritis is mixed with small‑to‑moderate, short‑term benefit at best and guideline recommendations remain inconsistent. Platelet‑rich plasma shows promising but heterogeneous results in early hip osteoarthritis; meta‑analyses suggest improvements comparable to hyaluronic acid at short‑term follow‑up, but protocols vary and certainty is low. Imaging guidance, strict asepsis, and patient selection (symptomatic flares with effusion/synovitis; failure of optimized conservative care) are crucial. Conclusion: In hip osteoarthritis, non‑pharmacologic care and simple analgesics/NSAIDs form the foundation. Intra‑articular Corticosteroids may be used for short‑term symptom control in selected patients; hyaluronic acid has uncertain value; platelet‑rich plasma remains investigational. A staged, shared‑decision pathway can individualize care while minimizing risk and avoiding premature surgery.